A nursing and midwifery training program in Kathmandu on antimicrobial resistance and stewardship and infection prevention and control: a qualitative and quantitative outcomes and process evaluation - Jamuna Tamrakar Sayami; Rakchya Amatya; Kshitij Karki; Deepak Bajracharya; Basudha Shrestha; Sreenidhi Srinivasan; Tyler Prentiss; Anita Shallal; Marcus Zervos; Katie Latack; Linda Kaljee (Frontiers in Public Health)
BackgroundLow- and middle-income countries (LMICs) are disproportionately affected by antimicrobial resistance (AMR). Nurses and midwives are essential to a holistic approach to AMR stewardship (AMS) and IPC within LMICs.Objective(1) Adapt AMS and IPC training programs and practice guidelines for community- and hospital-based nurses and midwives in Nepal; (2) pilot and conduct training outcome and process evaluations.DesignA one-day training was developed through partnerships between Henry Ford Health and nursing and midwifery organizations and teaching facilities in Nepal. Quantitative outcome and process evaluations were conducted. Qualitative process evaluation interviews were conducted with purposefully selected trainees.Setting(s)Trainees worked in healthcare facilities in Kathmandu Valley.ParticipantsA total of 126 nurses and midwives participated in the training and the quantitative evaluation. Eighteen trainees participated in the process evaluation interviews.MethodsThe 10-module program was adapted from AMS and IPC materials from the World Health Organization and the Nepal Ministry of Health and Population, and curricula from previous AMS studies in Nepal. Key outcomes were AMS and IPC knowledge, and decision-making about empirical dispensing of antibiotics. The process evaluation focused on training content, integration into practice, implementation barriers, and recommendations for dissemination. Quantitative data analysis included descriptive and bivariate analysis. Qualitative data analysis included coding, searches, review of coded texts, and identification of patterns and themes.ResultsAMS and AMR knowledge increased at immediate [1.40 (1.06–1.74) CI 95%] and six-month post-training [0.71 (0.35–1.08) CI 95%]. IPC knowledge also increased at immediate [0.79 (0.55–1.03) CI 95%] and six-month post-training [0.72 (0.49–0.96) CI 95%]. At immediate post-training, an increasing number of respondents indicated that they would not dispense antibiotics for adults [14.74% (4.88, 24.60%) CI 95%] and children [8.13% (−1.88, 18.14%) CI 95%] with fever and sore throats, and for non-pregnant women with burning sensation when urinating [10.69% (0.68%, 20.71%) CI 95%]. Process evaluation data indicated positive responses to the training content and relevancy to practice.ConclusionThe AMS-IPC training increased knowledge and decreased intentions for dispensing antibiotics. Participants provided concrete examples of implementation of learnings into practice. Trainings will be adapted to address identified content needs and challenges to implementation.